The emergence of the reformist trend in China in the period 1885-1895 (Journal of the College of Basic Education, 2023)
The Chinese have always viewed their intellectual approach as the pinnacle of human thinking, and their cultureThe highest culture in existence, indeed perhaps the only one, and that their emperor is the son of heaven, and what other peoples- including western countries - except for (barbaric savages) who deserve to recognize the sovereignty of the Son of Heaventhem, but after China opened up to the outside world after isolation that lasted for more than two centuries,A series of wars waged against it by Britain, France and the United States, and defeated itand forced it to sign a series of unequal treaties, in which it detracted from the imperial sovereignty.The center - China - and forced it to open its doors forcibly to trade, proselytizing and diplomatic exchange. AfterAll of this, did the Chinese remain so proud of their way of thinking, especially after their failure?in the face of these challenges? Were they affected by the civilization of those countries with which they were forced to come into contact?Did they find a solution to the problems of China in Western civilization? And if so, did they abandon civilization?Chinese, or did they make it the basis for reform? … This is what we tried to answer in this article.Pages that dealt with an important part of the history of modern China, which did not receive sufficient attention before.our researchers, although more research and fact-finding is needed to fill part of the blankwhich our libraries in particular and Arab libraries in general suffer from, relying on a number ofArabic, Chinese, French, and English documented sources that were directly approved.on Chinese documents written by Chinese officials in state departments, and memorandums raised byThe ambassadors of those countries in Beijing to their governments, as well as the writings of missionaries and travelers that covered partimportant from the history of modern China